EFFECTS OF TWEEN 80 ON PROTEASE PRODUCTION BY Candida lipolytica - Nascimento, Aline; Nascimento, Allana; Campos Takaki, G. (Boletín Micológico, 1997)
The influence of Tween 80, a non ionic tensoactive agent on extracelular protease produced by Candida lipolytica was investigated. The microorganism was grown in a medium containing different surfactant concentrations added to culture at different intervals of growth. The addition of the surfactant on the C. lipolytica culture medium, resulted in a in increase of intracelular and extracelular protease activity as wel as in an increase in the growth of the fingi which could be related to Tween 80 concentration and addition time.